Device Design of Doping‐Controlled Homojunction Perovskite Solar Cells Omitting HTL and Exceeding 25% Efficiency. Issue 2 (13th December 2020) - Lin, Lingyan; Li, Ping; Kang, Zhenjing; Xiong, Hao; Chen, Yiting; Yan, Qiong; Jiang, Linqin; Qiu, Yu
Abstract: Hole‐transport‐layer (HTL)‐free carbon‐based perovskite solar cells (C‐PSCs) have attracted great attention due to their low production cost and simplified structure. Nevertheless, C‐PCSs have not yet realized the high conversion efficiency achieved in conventional PSCs with HTLs. A new design of n‐CH3 NH3 PbI3 /p‐CH3 NH3 PbI3 homojunction is presented to attempt high efficiency HTL‐free C‐PSCs and its operation as a device is analyzed using solar cell capacitance simulator (SCAPS). Several parameters that can affect the device performance, such as perovskite layer doping concentration, thickness values, carrier mobility, and defect density, are explored and optimized. Under optimized conditions, a high power conversion efficiency of 25.07%, 15.6% relatively higher than conventional C‐PSC, can be obtained, indicating that the proposed homojunction‐based C‐PSC is promising because it highly simplifies the device structure and fabrication while maintaining high efficiency. This work points a way to commercialize HTL‐free PSCs for future industrial photovoltaics. Abstract : A numerical study of novel carbon‐based hole‐transport‐layer‐free perovskite solar cells with n‐CH3 NH3 PbI3 /p‐CH3 NH3 PbI3 homojunction as absorber is performed. Simulation results indicate that the optimal doping concentrations of n‐CH3 NH3 PbI3 and p‐CH3 NH3 PbI3 are 10 15 and 10 19  cm –3, respectively. After optimization, efficiency up to 25.07% can be obtained, much higher than conventional carbon‐based perovskite solar cells.